EVALUATION OF MAIL MANAGEMENT INFORMATION SYSTEM IMPLEMENTATION AT BRAWIJAYA UNIVERSITY USING THE HOT-FIT MODEL APPROACH - Muhammad Rosyihan Hendrawan; Rizqi Maulana (Fihris: Jurnal Ilmu Perpustakaan dan Informasi, 2022)
Mail activities are considered a highly essential information source for an agency. In short, mail must be adequately governed to maintain the high-value information that lies in it. In this era, mail governance has massively involved technologies in the mail management system. In the Brawijaya University Head Office, the correspondence governance has been managed with the assistance of an information system on correspondence management named Smart Collaborative Office (SCO). In practice, some barriers lead to the optimal implementation of this SCO. Therefore, this research evaluates SCO implementation to discover the supporting factors and barriers to implementing information systems in mail management. This research aims to perform an in-depth evaluation of the implementation of the SCO. And the research objectives are to discover the analysis result based on the HOT-Fit Model and the supportive and barrier factor of the SCO implementation in the Head Office of Brawijaya University. This research used an evaluative method with a qualitative approach. The evaluation model uses the HOT-Fit Model, with 35 people as a sample. The data collection uses questionnaires, interviews, observation, documentation, and literature study. The data was analyzed with a measurement model and structural model. The research shows that SCO implementation receives support from the higher-ups, easy-to-learn and easy-to-modified, support the multi-platform, with local and mandatory characteristics. However, the SCO still lacked advantages. One of them is inequal basic training for the users. The developer's competence with a lack of specialization in document or records management, unclean software-generated output, and sometimes, the software result data is not by the input data.